Betaine alleviates scleral remodeling in experimental myopia by regulating the TLR4/TAK1/NF-κB signaling pathway - Yinqiao Zhang; Yunxiao Xie; Zhaohui Yang; Runze Gao; Shuwen Yu; Jiawen Hao; Zhongyu Ma; Yuanting Yang; Ruixue Zhang; Hongsheng Bi; Dadong Guo (Toxicology and Applied Pharmacology, 2026)

Adsorption behavior and interaction mechanism of iodide and Pb2+ on a polyethyleneimine-glutaraldehyde aerogel: Batch experiments in aqueous solution and concentrated seaweed juice - Yu Liu; Runze Li; Jiahao Xie; Bangfeng Yin; Zuomiao Yang; Haijiao Xie; Hang Qi (Food Research International, 2026)

Transparent Cu mesh electrodes produced using a laser-direct-written reusable ITO grid template - Kaibo Yu; Bin Yang; Miao Li; Yu Zhang; Mengxiang Liu; Zihao Chen; Runze Zhang; Jiale Fan; Zihan Kong; Tao Zhang (Chemical Engineering Journal, 2026)

A homogenized gridded climate dataset for China - Kaicun Wang; Hongze Cai; Yanyi He; Yun Li; Hanmeng Xia; Changjian Yin; Hongyong Yu; Runze Zhao; Zhengtai Zhang; Chunlüe Zhou (Science China Earth Sciences, 2026)

Flexotronic effect-triggered channel switching for high-sensitivity mechanical sensing - Jinwan Chen; Qing Zhao; Zhuangzhuang Zhang; Rui Ge; Hao Sun; Yongkang Zhang; Runze Yu; Longfei Wang; Shuhai Liu (Science Bulletin, 2026)

Microplastics alter soil carbon sequestration pathways: Temporal shifts from microbial necromass to plant lignin dominance - Runze Feng; Hong Yu; Wenbing Tan (Journal of Environmental Chemical Engineering, 2026)

A novel thermostable and glucose tolerant β-glucosidase from Caldibacillus thermoamylovorans MB12B for efficient hydrolysis of lignocellulosic biomass - Longlin Meng; Yongxuan Liu; Xiaowen Sun; Runze Ma; Xiaowei Chen; Chunjie Gong; Xun Yu (International Biodeterioration & Biodegradation, 2026)

Data-driven discovery of high-performance surface passivators for efficient and stable perovskite solar cells - Feiyi Zhou; Zeyu Wang; Shangshang Zhao; Xu Zhang; Qingyue Guo; Runze Dai; Fanxiang Meng; Huajie Lyu; Jun Wan; Yi Dong; Zhe Jin; Shanqing Yu; et al. (Chemical Engineering Journal, 2026)

Landscape composition, but not landscape configuration, improve the biological control service in pomelo agroecosystems - Jie Zhang; Peng Huang; Yi Zhao; Saiyang Liu; Runze Liu; Jinai Yao; Deyi Yu (Agriculture, Ecosystems & Environment, 2026)

Emissions of fully fluorinated greenhouse gases in central-eastern China inferred from atmospheric observations - Qianna Du; Xiaoyi Hu; Runze Zhu; Zifa Wang; Bowei Li; Liting Hu; Zhouxiang Cai; Mingrui Ji; Jingtao Xu; Haibo Yu; Yunxing Hu; Bo Yao; et al. (Journal of Environmental Management, 2026)

Buried interface engineering for efficient and stable inverted perovskite solar cells - Li Pan; Runze Yu; Zhu Fang; Bin Chen; Liya Zheng; Runxin Hu; Gang Chen (Chemical Engineering Journal, 2025)

Research progress in the technology of active substance extraction from red algae - Jinqi Qu; Runze Liu; Wensong Yu; Wenjun Li; Chenyang Lu; Song Qin (Algal Research, 2025)

Enhancing tree-based machine learning for chlorophyll-a prediction in coastal seawater through spatiotemporal feature integration - Tongcun Liu; Guochun Yu; Hoi Yan Kwok; Runze Xue; Ding He; Wenzhao Liang (Marine Environmental Research, 2025)

Performance evaluation of La-Al bimetallic catalyst-assisted dielectric barrier discharge plasma degradation of sulfur hexafluoride - Jiaqi Li; Dinghao Deng; Runze Dong; Qian Yu; Dong Fu (Journal of Environmental Chemical Engineering, 2025)

Revealing the entanglement between pectin and silver carp myofibrillar protein molecular chains: A new perspective on the effect of solubilization mode on gel properties - Han Yu; Xiyu Yu; Xin Guo; Runze Li; Hui Li; Jian Zhang (Food Research International, 2025)

The research on the evaluation framework and application of urban three-dimensional (aboveground and underground) regeneration sensitivity——Taking Kunshan Old City in China as an example - Kunyang Li; Jizhong Shao; Runze Lin; Guan Liu; Yu Zhang; Minge Yang (Tunnelling and Underground Space Technology, 2025)

Machine learning-assisted rapid electromagnetic design of flexible graphene-based absorptive composites - Runze Zhang; Ye Yuan; Xiaohan Wang; Xianxian Sun; Shasha Wang; Zibo Yang; Yu Ma; Enshuang Zhang; Yibin Li (Chemical Engineering Journal, 2025)

Investigation of crevice corrosion susceptibility of L80-13Cr in CO2 solution containing SO2 - Yu Yuan; Runze Jia; Pengfei Hao; Fengyu Zhang; Yongyang Zhao; Chen Li; Yong Xiang (International Journal of Greenhouse Gas Control, 2025)

Modeling of wave-induced drift based on stepwise parameter calibration - Kui Zhu; Xueyao Chen; Lin Mu; Dingfeng Yu; Runze Yu; Zhaolong Sun; Tong Zhou (Frontiers in Marine Science, 2025)
The motion of waves in water causes the slow movement of drifting sea targets—a phenomenon usually ignored in target-drift prediction models for maritime search and rescue (SAR). This study examined the wave-induced drift’s influence on field-observation experiments involving two common, differently sized SAR targets—an offshore fishing vessel (OFV) and a person in the water (PIW)—using parameter stepwise calibration and machine-learning (ML) methods. The sample of wave-induced drift velocity was obtained by gradually separating current-induced (CI) drift’s and wind-induced (WI) drift’s influence from the target-drift velocity using the least-square method and AP98 model. A force analysis method and three ML methods, long short-term memory (LSTM), back-propagation (BP) neural network, and random forest (RF), were used to fit the wave-induced drift velocity by combining eight different parameter schemes. Finally, the drift trajectories considering the influence of waves were fitted and verified based on 2 independent samples respectively. Compared with the force analysis method, the accuracy of the ML methods in the verification test was higher. In addition, the results show that for OFVs, considering wave-induced drift’s influence in the ensemble-trajectory prediction could improve the simulation accuracy. However, for a PIW, no significant improvement was observed. This result also indicates that wave-induced drift may not be simply ignored in large SAR targets’ drift prediction.

Identification of dehydrin family genes in three Medicago species and insights into their tolerant mechanism to salt stress - Xiuxiu Zhang; Xiuzhi Xia; Yu Sun; Runze Wang; Kemeng Liang; Yarong Wang; Lifei Ren; Qin Wang (Plant Cell Reports, 2025)

Corrigendum to “Novel Diphenyl urea derivative serves as an inhibitor on human lung cancer cell migration by disrupting EMT via Wnt/β-catenin and PI3K/Akt signaling” [Toxicology in Vitro 69 (2020) 105000] - Bingling Dai; Mengying Fan; Runze Yu; Qi Su; Bo Wang; Tianfeng Yang; Feng Liu; Yanmin Zhang (Toxicology in Vitro, 2024)

Experimental investigation on the dynamic response of vent plate under methane-air mixtures explosion load - Runze Yu; Yanyu Qiu; Huadao Xing; Guangan Xu; Mingyang Wang; Bin Li; Lifeng Xie; Song Sun (Engineering Structures, 2024)

Correlating working performance with thermal comfort, emotion, and fatigue evaluations through on-site study in office buildings - Yaowen Liang; Jiangpeng Yu; Runze Xu; Jingsi Zhang; Xiang Zhou; Maohui Luo (Building and Environment, 2024)

Ultralight, low-shrinkage copolyimide aerogels with excellent mechanical strength for flexible thermal protection - Yu Chen; Baolu Shi; Runze Jin; Xinqiao Wang; Donghui Guo; Zhiliang Zhou; Baosheng Xu; Ning Zhou (Chemical Engineering Journal, 2024)

Full-chain analysis on emerging contaminants in soil: Source, migration and remediation - Lu Liu; Chunrui Liu; RunZe Fu; Fandi Nie; Wei Zuo; Yu Tian; Jun Zhang (Chemosphere, 2024)

Effect of apple high-methoxyl pectin on heat-induced gelation of silver carp myofibrillar protein - Han Yu; Yunfeng Zhao; Runze Li; Xin Guo; Pingping Liu; Jian Zhang (Food Chemistry, 2024)

Numerical study on rotating detonation combustion with the discrete distribution of partially pre-vaporized n-heptane sprays - Huangwei Chen; Runze Li; Yu Wu; Hongbo Hu; Yuejin Zhu (Fuel, 2024)

Differences in three instars of four carrion nitidulids (Coleoptera, Nitidulidae, Nitidula and Omosita) revealed using SEM - Gengwang Hu; Chao Liu; Runze Zhang; Liangliang Li; Shipeng Shao; Ruonan Zhang; Yundi Gao; Yi Guo; Ya Yang; Yu Wang; Luyang Tao (Arthropod Structure & Development, 2024)

Particulate organic carbon potentially increases methane emissions from oxic water of eutrophic lakes - Chuanqiao Zhou; Muchun Zhou; Ruoyu Jia; Yu Peng; Fenjun Zhao; Runze Xu; Shuoyuan Liang; Akihiko Terada; Guoxiang Wang; Tsuyoshi Kinouchi; Xiaoguang Xu (Science of The Total Environment, 2023)

Probabilistic modelling of surface drift prediction in marine disasters based on the NN–GA and ARMA model - Kui Zhu; Lin Mu; Runze Yu; Xiaoyu Xia; Haiwen Tu (Ocean Engineering, 2023)

Dual-channel molecularly imprinted sensor based on dual-potential electrochemiluminescence of Zn-MOFs for double detection of trace chloramphenicol - Yu Zhao; Runze Wang; Yuehui Wang; Guifen Jie; Hong Zhou (Food Chemistry, 2023)

Deep Sc-RNA sequencing decoding the molecular dynamic architecture of the human retina - Lulin Huang; Runze Li; Lin Ye; Shanshan Zhang; Huaping Tian; Mingyan Du; Chao Qu; Shujin Li; Jie Li; Mu Yang; Biao Wu; Ran Chen; et al. (Science China Life Sciences, 2023)

Migration characteristics and ecological risk assessment of heavy metals in ash from sewage sludge co-combustion in coal-fired power plants - Shilin Yu; Runze Tao; Houzhang Tan; Ao Zhou; Shuanghui Deng; Xuebin Wang; Qingfu Zhang (Fuel, 2023)

Soil apparent electrical conductivity and must carbon isotope ratio provide indication of plant water status in wine grape vineyards - Runze Yu; Daniele Zaccaria; Isaya Kisekka; S. Kaan Kurtural (Precision Agriculture, 2021)
Proximal sensing is being integrated into vineyard management as it provides rapid assessments of spatial variability of soils’ and plants’ features. The electromagnetic induction (EMI) technology is used to measure soil apparent electrical conductivity (EC a ) with proximal sensing and enables to appraise soil characteristics and their possible effects on plant physiological responses. This study was conducted in a micro irrigated Cabernet Sauvignon ( Vitis vinifera L.) vineyard to investigate the technical feasibility of appraising plant water status and its spatial variability using soil EC a and must carbon isotope ratio analysis (δ 13 C). Soil temperature and soil water content were monitored in-situ using time domain reflectometry (TDR) sensors. Soil EC a was measured with EMI at two depths [0–1.5 m (deep EC a ) and 0–0.75 m (shallow EC a )] over the course of the crop season to capture the temporal dynamics and changes. At the study site, the main physical and chemical soil characteristics, i.e. soil texture, gravel, pore water electrical conductivity (EC e ), organic carbon, and soil water content at field capacity, were determined from samples collected auguring the soil at equidistant points that were identified using a regular grid. Midday stem water potential (Ψ stem ) and leaf gas exchange, including stomatal conductance ( g s ), net carbon assimilation ( A n ), and intrinsic water use efficiency (WUE i ) were measured periodically in the vineyard. The δ 13 C of produced musts was measured at harvest. The results indicated that soil water content (relative importance = 24%) and texture (silt: relative importance = 22.4% and clay: relative importance = 18.2%) were contributing the most towards soil EC a . Deep soil EC a was directly related to Ψ stem (r 2 = 0.7214) and g s (r 2 = 0.5007). Likewise, δ 13 C of must was directly related to Ψ stem (r 2 = 0.9127), g s (r 2 = 0.6985), and A n (r 2 = 0.5693). Results from this work provided relevant information on the possibility of using spatial soil EC a sensing and δ 13 C analysis to infer plant water status and leaf gas exchange in micro irrigated vineyards.

Rhizosphere microbiome modulated effects of biochar on ryegrass 15N uptake and rhizodeposited 13C allocation in soil - Yingyi Fu; Amit Kumar; Lijun Chen; Yuji Jiang; Ning Ling; Runze Wang; Qiong Pan; Bhupinder Pal Singh; Marc Redmile-Gordon; Lu Luan; Qin Li; Quan Shi; et al. (Plant and Soil, 2021)

Effect and threshold of PM2.5 on population mortality in a highly polluted area: a study on applicability of standards - Runze Ye; Liangliang Cui; Xiumiao Peng; Kunkun Yu; Fang Cheng; Yakun Zhu; Chongqi Jia (Environmental Science and Pollution Research, 2019)

Laboratory test on crack development in mudstone under the action of dry-wet cycles - Ming Hu; Yuanxue Liu; Jianbo Ren; Runze Wu; Yu Zhang (Bulletin of Engineering Geology and the Environment, 2019)

Gene expression profiling of human hepatocytes grown on differing substrate stiffness - Tingting Xia; Runze Zhao; Fan Feng; Yijiang Song; Yu Zhang; Lili Dong; Yonggang Lv; Li Yang (Biotechnology Letters, 2018)

Temperature-Induced Deterioration Mechanisms in Mudstone during Dry–Wet Cycles - Ming Hu; Yuanxue Liu; Jianbo Ren; Yu Zhang; Runze Wu (Geotechnical and Geological Engineering, 2017)